INOVASI DI INDUSTRI ECERAN : MAMPUKAH BERPERAN SEBAGAI MEDIATOR ANTARA ORIENTASI PASAR DAN KINERJA ORGANISASI - Raharso, Sri (JURNAL BISNIS STRATEGI, 2006)
Market orientation has been identified as a managerial focus which can enhance firm performance.Â  However, this assumption increasingly is met with skepticism. There is no unequivocal evidence as to if and when market orientation has a positive impact on business performance. The exact mechanisms concerning performance enhancement are not fully understood. Current research proposes that the mechanisms by which market orientation enhances performance relies on the existence of aninnovative culture.Â  Innovativeness mediates the relationship between market orientation and performance.